Knowledge, attitudes, and practices regarding body weight management among patients with overweight or obesity: a cross-sectional study - Wenjun Shi; Cuiliu Ma; Guishan Zhang; Zhijiao Xu; Xing Liu; Yang Li; Cuijing Zhang (Frontiers in Public Health)
ObjectivesThis study aimed to investigate the knowledge, attitudes, and practices (KAP) related to weight management among overweight or obese patients.MethodsA cross-sectional study was conducted in May 2024 at the First Hospital of Zhangjiakou, focusing on overweight or obese patients. Self-administered questionnaires were used to collect demographic data and assess participants' KAP scores.ResultsA total of 527 valid responses were obtained, with 299 (56.74%) respondents being female. The mean scores for knowledge, attitudes, and practices were 6.09 ± 2.93 (possible range: 0–11), 22.79 ± 3.02 (possible range: 8–40), and 32.89 ± 9.72 (possible range: 9–45), respectively. Correlation analysis revealed a significant positive relationship between knowledge and practices (r = 0.305, P < 0.001), and a negative relationship between attitudes and practices (r = −0.516, P < 0.001). Structural equation modeling showed that knowledge directly influenced attitudes (β = 0.897, P = 0.008), and attitudes directly influenced practices (β = 1.108, P = 0.008). Additionally, knowledge had an indirect effect on practices through attitudes (β = 0.994, P = 0.007).ConclusionsOverweight or obese patients demonstrated inadequate knowledge, negative attitudes, and proactive practices toward weight management. These findings highlight the need for targeted educational interventions to enhance weight management knowledge and foster positive attitudes, ultimately leading to improved health practices within this population.